Synthesis and Properties of a Polymer-Modified Material for Thin Spray-On Liners in Mine Roadways - Lianjun Chen; Xuekai Jiang; Zhaoxia Liu; Xiangfei Cui; Guoming Liu; Zhi Zhou; Qizheng Dong (Advances in Materials Science and Engineering)
In order to adapt to dry and wet environment in mine roadways and improve the performance of sealing materials under different environmental conditions, this study selected the materials based on their ability to spray and found that the materials with a viscosity of 1500–6000 MPa·s can achieve a balance between performance of spray and wall-hanging performance. Next, by selecting high-elastic polyacrylate emulsion and ordinary Portland cement as the film-forming agent and gel, respectively, mix proportion factors of the nonreactive thin spray-on liner (TSL) were analyzed by using the Taguchi method. Moreover, fluidity, setting time, sealing properties, compressive strength, bending strength, and bonding strength of those materials were measured. It was disclosed that addition of an appropriate amount of polyacrylate emulsion can enhance the effects of fibers. By observing the morphologies of the materials’ bonding surfaces and comparing the factors influencing bonding strength between both dry and wet walls, it was uncovered that the adhesive property of cement-based sealing materials was mainly affected by the water-cement ratio. Eventually, bonding strength and sealing properties were selected as primary optimization indexes, while setting time, bending strength, and compressive strength were selected as secondary optimization indexes. The appropriate proportions of two types of TSLs for dry and wet walls were (W/C = 50%; P/C = 6%; F/C = 1%; T/C = 0.2%) and (W/C = 45%; P/C = 6%; F/C = 1%; T/C = 0.4%), respectively. A prepared TSL can be used for filling rock fractures in mine roadways. In addition, TSL exhibited a great performance for dry and wet walls under different environmental conditions. The present study may provide an insightful guidance and reference for the investigation of TSL sealing materials applied in the mine roadways.